SURFACE PROPERTIES, SOLUBILITY AND DISSOLUTION KINETICS OF BAMBOO PHYTOLITHS - Fraysse F.; Pokrovsky O.S.; Schott J.; Meunier J.D. (My University, 2006)
Although phytoliths, constituted mainly by micrometric opal, exhibit an important control on silicon cycle in superficial continental environments, their thermodynamic properties and reactivity in aqueous solution are still poorly known. In this work, we determined the solubility and dissolution rates of bamboo phytoliths collected in the Réunion Island and characterized their surface properties via electrophoretic measurements and potentiometric titrations in a wide range of pH. The solubility product of "soil" phytoliths ( p Ksp0 = 2.74 at 25 °C) is equal to that of vitreous silica and is 17 times higher than that of quartz. Similarly, the enthalpy of phytoliths dissolution reaction ( Δ Hr25 - 80 ° C = 10.85 kJ / mol ) is close to that of amorphous silica but is significantly lower than the enthalpy of quartz dissolution. Electrophoretic measurements yield isoelectric point pHIEP = 1.2 ± 0.1 and 2.5 ± 0.2 for "soil" (native) and "heated" (450 °C heating to remove organic matter) phytoliths, respectively. Surface acid-base titrations allowed generation of a 2-pK surface complexation model. Phytoliths dissolution rates, measured in mixed-flow reactors at far from equilibrium conditions at 2 {less-than or slanted equal to} pH {less-than or slanted equal to} 12, were found to be intermediate between those of quartz and vitreous silica. The dissolution rate dependence on pH was modeled within the concept of surface coordination theory using the equation:{A formula is presented}where {>i} stands for the concentration of the surface species present at the SiO2-H2O interface, ki are the rate constants of the three parallel reactions and n and m represent the order of the proton- and hydroxy-promoted reactions, respectively. It follows from the results of this study that phytoliths dissolution rates exhibit a minimum at pH ~ 3. This can explain their good preservation in the acidic soil horizons of Réunion Island. In terms of silicon biogeochemical cycle, phytoliths represent a large buffering reservoir, which can play an important role in the regulation of silica fluxes in terrestrial aquatic environments. © 2006 Elsevier Inc. All rights reserved.